Whiplash syndrome and forensic approach. A case report - Nancy Peña; Óscar Sánchez Cardozo (Case Reports)
The same day as being involved in a traffic incident as a pedestrian hit by a car, a middle-aged woman accessed emergency medical care and was later discharged. After two days the patient returned to emergency with complaints of neck pain. X-rays were conducted was immobilized with a cervical collar. Since the pain persisted, she was examined a few days later by physiatry, where a limitation in the arc of motion of the neck was found and whiplash was considered a possibility.